Measuring the multilingual reality: lessons from classrooms in Delhi and Hyderabad - Lightfoot, Amy; Balasubramanian, Anusha; Tsimpli, Ianthi; Mukhopadhyay, Lina; Treffers-Daller, Jeanine (International journal of bilingual education and bilingualism, 2022)
India's linguistic diversity is reflected in classrooms across the country, where multiple languages are used by teachers and learners to negotiate meaning and instruction - a multilingual, multicultural student body is the norm, whether in urban or rural contexts. This study documents teaching practices in English language and maths lessons in Delhi and Hyderabad, with a specific focus on language use. The findings from 104 classroom observations allow us to profile multilingual practices used in schools with different official mediums of instruction. Results reveal a predominant use of 'language mixing' in the classroom, in both English- and regional language-medium of instruction contexts - especially in English subject lessons. Maths lessons in regional-medium schools did not involve as much language mixing by the teachers but this was still a strong feature for learners. The data also shows differences between language use particularly when comparing English-medium schools in each city. Specifically, lessons in Delhi were characterised by absolutely no occurrences of English used on its own by the teachers (as recorded during five-minute intervals), compared to significantly greater use of English alone in Hyderabad English-medium and Telugu-medium schools. Delhi teachers appear to use a greater amount of language mixing during each lesson.